Genome-Wide Identification, Phylogeny, and Expression Analyses of the 14-3-3 Family Reveal Their Involvement in the Development, Ripening, and Abiotic Stress Response in Banana - Li, Meiying; Ren, Licheng; Xu, Biyu; Yang, Xiaoliang; Xia, Qiyu; He, Pingping; Xiao, Susheng; Guo, Anping; Hu, Wei; Jin, Zhiqiang (Frontiers in Plant Science, 2016)
Plant 14-3-3 proteins act as critical components of various cellular signaling processes and play an important role in regulating multiple physiological processes. However, less information is known about the 14-3-3 gene family in banana. In this study, 25 14-3-3 genes were identified from the banana genome. Based on the evolutionary analysis, banana 14-3-3 proteins were clustered into ε and non-ε groups. Conserved motif analysis showed that all identified banana 14-3-3 genes had the typical 14-3-3 motif. The gene structure of banana 14-3-3 genes showed distinct class-specific divergence between the ε group and the non-ε group. Most banana 14-3-3 genes showed strong transcript accumulation changes during fruit development and postharvest ripening in two banana varieties, indicating that they might be involved in regulating fruit development and ripening. Moreover, some 14-3-3 genes also showed great changes after osmotic, cold, and salt treatments in two banana varieties, suggested their potential role in regulating banana response to abiotic stress. Taken together, this systemic analysis reveals the involvement of banana 14-3-3 genes in fruit development, postharvest ripening, and response to abiotic stress and provides useful information for understanding the functions of 14-3-3 genes in banana.